2021
DOI: 10.21037/qims-20-873
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes on liver proton density fat fraction differ between liver segments

Abstract: Background: To study the spatial heterogeneity of liver fat fraction changes during a long-term lifestyle intervention study using magnetic resonance imaging (MRI).Methods: Thirty-two subjects underwent two MRI-scans in a span of one year. A chemical shift encodingbased water-fat separation method was applied to measure liver proton density fat fraction (PDFF) maps.The PDFF changes in the two liver lobes and the Couinaud segments were compared with the mean liver PDFF change.Results: The slope of the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Interestingly, in 1 H MRI studies, it has also been shown that the proton density fat fraction varies over the liver and that it is significantly higher in the right lobe than in the left lobe in subjects with NAFLD, obesity, or at a high risk of developing type 2 diabetes, which was speculatively associated with differences in perfusion of and/or different contributions of mesenteric versus splenic blood supply to the right and left liver lobe. [51][52][53] The observed spatial differences in 31 P metabolites across the liver will be important to take into account when assessing (the progression of) liver disease and monitoring therapy response with 31 P MRS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in 1 H MRI studies, it has also been shown that the proton density fat fraction varies over the liver and that it is significantly higher in the right lobe than in the left lobe in subjects with NAFLD, obesity, or at a high risk of developing type 2 diabetes, which was speculatively associated with differences in perfusion of and/or different contributions of mesenteric versus splenic blood supply to the right and left liver lobe. [51][52][53] The observed spatial differences in 31 P metabolites across the liver will be important to take into account when assessing (the progression of) liver disease and monitoring therapy response with 31 P MRS.…”
Section: Discussionmentioning
confidence: 99%
“…A possible way to solve this problem is to suppress the fat signal using fat saturation, inversion recovery (IR), or water excitation techniques (11)(12)(13). However, the fat signal also has diagnostic values under certain circumstances (14)(15)(16). Another idea is to separate water and fat by postprocessing the chemical shift-encoded (CSE) data (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on the Dixon method, a variety of improved methods for water-fat separation have been developed (20)(21)(22)(23)(24). Water-fat separation methods can eliminate the effects of the fat in T1 mapping and also allow the quantification of fat, which is useful for diagnosing fatty liver disease (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Previously chemical shift encoding-based fat quantification was introduced as a MR-based technique that has been applied for the assessment of muscle composition [ 8 ], since this technique allows the measurement of the MR-based proton density fat fraction (PDFF), as well as vertebral T2* values. Although MR-based mapping techniques have shown to be useful for the assessment of various body tissues, including, e.g., T2* mapping in order to assess iron depositions within the brain [ 9 ] or T2 mapping for assessment of cartilaginous tissue [ 10 ], chemical shift encoding-based fat quantification has been considered to be a promising tool for the assessment of the fatty infiltration of muscles and liver [ 11 ], as well as for the assessment of vertebral bone marrow water-fat composition [ 12 , 13 , 14 ]. In contrast to the computed tomography (CT), during the MR-based assessment of vertebral bone marrow water-fat composition, the patient is not exposed to radiation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%